2002
DOI: 10.1097/00000478-200203000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Sentinel Lymph Node Processing in Breast Cancer

Abstract: The status of the sentinel lymph node (SLN) has been shown to accurately reflect the presence or absence of metastases in the axilla in patients with breast cancer. This study was designed to determine the optimal protocol for SLN processing. A total of 173 SLNs from 96 breast cancer patients who had successful SLN localization and underwent completion axillary node dissection were identified. All SLNs were negative for metastases by initial routine histologic evaluation. The nodes were submitted in a total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Permanent section histologic evaluations are reported to miss at least 10% to 15% of metastases >.2 mm because of practical limitations in sampling [7] and [12]. The same sampling errors necessarily contribute to the lack of perfect agreement between the BLN Assay and the OHR.…”
Section: Resultsmentioning
confidence: 99%
“…Permanent section histologic evaluations are reported to miss at least 10% to 15% of metastases >.2 mm because of practical limitations in sampling [7] and [12]. The same sampling errors necessarily contribute to the lack of perfect agreement between the BLN Assay and the OHR.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the majority of metastases will be detected in the first few sections examined (Cserni, 2002;Yared et al, 2002). Yared et al (2002) examined 10 levels of serially sectioned SLNs and performed IHC on levels 3 and 8, while the remaining levels were stained with H&E. The authors found that the first two H&E or the first cytokeratin-stained levels were positive for metastases in 96%.…”
Section: Discussionmentioning
confidence: 99%
“…Yared et al (2002) examined 10 levels of serially sectioned SLNs and performed IHC on levels 3 and 8, while the remaining levels were stained with H&E. The authors found that the first two H&E or the first cytokeratin-stained levels were positive for metastases in 96%. Two additional H&E-stained and one cytokeratin-stained level of each SLN correctly identified the status of the node in 98% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Two of these sections were stained with H & E for the verification of the standard histopathologic results (e.g., the first and third), and the others (e.g., Numbers 2 and 4) were stained by immunohistochemistry. Immunohistochemical staining was performed with antipancytokeratin antibodies (primary murine polyclonal anti-human-keratins antibodies, clones AE1, AE3, and PCK2, dilution 1:100) following the standard procedure established for an automatized system (Nexes ® , Tucson, AZ).…”
Section: Methodsmentioning
confidence: 99%